Efficiency of single stage- and two stage pretreatment in biomass with different lignin content. (July 2016) - Kärcher, M.A.; Iqbal, Y.; Lewandowski, I.; Senn, T.
Highlights: Single stage pretreatment had higher enzymatic glucose yields in wheat straw. Two stage pretreatment had higher enzymatic glucose yields in miscanthus. Lignin content was key factor affecting single/two stage pretreatment performance. Abstract: In current study the enzymatic glucose yields of miscanthus and wheat straw were compared after single stage- and two stage pretreatment with dilute sulfuric acid at different pretreatment severities. Glucose yields after two stage pretreatment were higher than after single stage pretreatment in miscanthus. Whereas wheat straw had higher glucose yields after single stage pretreatment. The study shows that two stage pretreatment has a negative effect on glucose yield in biomass with low not-acid-degradable lignin content and a positive one in biomass with high not-acid-degradable lignin content. The not-acid-degradable lignin fraction offers a higher degree of protection of the whole lignin structure against chemical attacks by mineral acids. More severe pretreatment conditions were needed to achieve a sufficient breakup of the lignin structure. But more severe conditions enhance resin formation, leading to lower enzyme activity and reduced carbohydrate yields.